Association between game metrics in a simulation game and nursing students' surgical nursing knowledge - a quasi-experimental study - Koivisto, Jaana-Maija (BMC, 2025)
BackgroundSimulation games are effective for acquiring surgical nursing knowledge during education by offering possibilities to learn theoretical knowledge through practical patient scenarios, thus preparing students for demanding surgical nursing care. Game metrics stored in the game system enable assessment of students' behaviour while gameplaying. Combining game metrics with the assessment of a student's surgical nursing knowledge allows versatile information to be obtained about the student's learning outcomes. However, studies on game metrics stored in systems and their relationship with learning outcomes are scarce.MethodsThe aim here was to evaluate the association between game metrics in a simulation game and nursing students' surgical nursing knowledge. Nursing students from three universities of applied sciences in Finland participated in a one-week simulation gameplaying intervention that included five surgical nursing scenarios. Students' surgical nursing knowledge was investigated with a quasi-experimental, one-group, pre- and post-test design using a surgical nursing knowledge test. In total, 280 students filled in the knowledge tests. In addition, cross-sectional game data were collected at a single time point between pre- and post-tests. The data were analysed with descriptive statistics and multivariate analysis methods.ResultsStudents' surgical nursing knowledge improved with the intervention. The total number of playthroughs was 3562. The mean maximum score was 126.2 (maximum score range 76-195). The mean playing time of all playthroughs by all players was 4.3 minutes (SD = 81.61). A statistically significant association was found between mean score and knowledge test total score (p < 0.0072), but no significant association emerged between mean playing time and knowledge test total score.ConclusionThe results indicated that the higher the mean score the better the students' surgical nursing knowledge in the knowledge test. This study did not show that the time spent playing had an impact on students' post-playing knowledge. Our findings support the idea that game metrics can be used in performance evaluation and the results can be used to improve nursing students' readiness for challenging preoperative and postoperative clinical situations.